Performance analysis of dual-media cooperative communication based on wireless and power line under hybrid fading - Zhixiong Chen; Yifang Jing; Dongsheng Han; Lijiao Wang (International Journal of Distributed Sensor Networks)
Wireless communication and power line communication are extensively applied in various fields, such as household Internet of things. For cooperative communication of amplify–forward relay using wireless access and power line transmission, the hybrid model of universal Nakagami wireless fading and lognormal power line fading was used in this study. A comparative analysis of similarities between Gamma and lognormal distributions and lognormal distribution characteristics of relay link signal-to-noise ratio was also carried out. Given the deficiencies of lognormal variable add approximation method, lognormal distribution parameters combined computing method based on moment generation function was proposed. Theoretical formulas of outage probability and bit error rate after amplify–forward relay and maximal-ratio combining was derived on the basis of moment generation function of the total output signal-to-noise ratio of the system. Effectiveness and reliability of the algorithm and theoretical formula were verified through simulation, and influence rules of hybrid channel fading and power distribution on the system performance were analyzed.